Effects of neuromuscular training on proprioception and muscular reaction time in older woman: Randomized controlled trial - Concha-Cisternas, Yeny; Pinero, Jose Castro; Celis-Morales, Carlos; Valdes-Badilla, Pablo; Nuñez-Espinosa, Cristian; Cigarroa, Igor; Salazar-Mendez, Joaquin; Alarcon-Rivera, Miguel; Guzman-Munoz, Eduardo (My University, 2025)
Background this study aimed analyze the effects of a neuromuscular training program compared to a multicomponent training program on proprioception and muscle reaction time in older woman. Material and methods Randomized controlled trial, included 54 older women randomized into 3 groups: multicomponent group (MCG), neuromuscular group (NMG), and control group (CG). Proprioception was assessed using the active repositioning test in the shoulder, elbow, hip, and knee joints. The muscular reaction time of the peroneus longus, tibialis anterior, and gastrocnemius medialis were evaluated. MCG carried out a multicomponent training program and, NMG realized neuromuscular training program plus the multicomponent training. Results A significant time x group interaction was observed in proprioception the shoulder joints (F = 7.57; p = 0.003; eta p(2) = 0.255), hip joints (F = 10.2; p = < 0.001; eta p(2) = 0.258) and knee (F = 7.12; p = 0.004; eta p(2) = 0.244) and reaction time of the peroneus longus (F = 13.7; p = < 0.001; eta p(2) = 0.378), tibialis anterior (F = 8.14; p = 0.002; eta p(2) = 0.246) and gastrocnemius medial (F = 7.86; p = 0.003; eta p(2) = 0.263). Multiple comparisons showed that there are significant improvements between the pre-and post-assessment of the NMG in proprioception and muscle reaction time. Conclusions Neuromuscular training program enhances the effects of multicomponent training and should be included in the physical activity programs of older people
Keywords: aged; active repositioning; rehabilitation; physical exercise; myography